2021
DOI: 10.4315/1541-9576-41.3.274
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of Consumers’ Risk Perception and Hygiene of Retail Meat: A Nigerian Study

Abstract: Consumers' perception of food safety risk could influence their food consumption habits. This questionnaire-based (n = 327) cross-sectional study assessed consumers' attitudes about and perception of retail meat risk. Also, the hygiene of meat display tables (n = 105) and retail meat (n = 107) sold to consumers was determined using total aerobic plate count and total coliform count.Most respondents were single (82.6%) and had tertiary educational status (89.3%). Most of the respondents preferred beef (60.9%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…However, the microbial profile of roasted beef in Abuja showed 54% of S. aureus (Amaeze et al 2016). These results showed that the meat was unfit for consumption and indicated poor sanitary and processing/handling practices as it is typically observed in most Nigerian slaughterhouses and retail environments (Adetunji and Odetokun 2011;Odetokun et al 2020;Odetokun et al 2021a,b).…”
Section: Factors Influencing S Aureus Contamination Of Food Of Animal...mentioning
confidence: 94%
“…However, the microbial profile of roasted beef in Abuja showed 54% of S. aureus (Amaeze et al 2016). These results showed that the meat was unfit for consumption and indicated poor sanitary and processing/handling practices as it is typically observed in most Nigerian slaughterhouses and retail environments (Adetunji and Odetokun 2011;Odetokun et al 2020;Odetokun et al 2021a,b).…”
Section: Factors Influencing S Aureus Contamination Of Food Of Animal...mentioning
confidence: 94%
“…(2) attitudes to the practice of antimicrobial usage; (3) risk perception of AMR. A numeric scoring system [20][21][22][23] was computed from a five-point Likert scale [24] to assess these outcome variables. A reverse scoring pattern was used where strongly disagree was the highest correct answer, scored as five.…”
Section: Data Management and Statistical Analysismentioning
confidence: 99%
“…Understanding the resistance patterns of S. aureus isolated from milk and cheese in Ilorin, Nigeria, can contribute to the local and national efforts to combat antibiotic resistance. Ensuring the safety and quality of food products, including dairy, is critical for maintaining consumer confidence in the food supply chain (Odetokun et al, 2021;Wu et al, 2021;. When consumers have access to information about the prevalence of S. aureus and its susceptibility to antibiotics in milk and cheese, they can make more informed choices about their food consumption.…”
Section: Introductionmentioning
confidence: 99%